2022
DOI: 10.3389/fpsyg.2021.647126
|View full text |Cite
|
Sign up to set email alerts
|

Common Predictive Factors of Social Media Addiction and Eating Disorder Symptoms in Female College Students: State Anxiety and the Mediating Role of Cognitive Flexibility/Sustained Attention

Abstract: This study aimed to investigate the common predictive factors between social media addiction (SMA) and eating disorder symptoms (EDS), in a group of Chinese female college students. A total of 216 students completed the behavioral assessments of cognitive flexibility and sustained attention, as well as the questionnaires on anxiety, social media dependence, and eating disorders. The results indicate that SMA is significantly correlated with EDS. Structural equation modeling was used to test the model in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Additionally to the aforementioned theoretical framework, empirical studies have shown that social media addiction predicts phubbing (Chi et al, 2022 ; Rahman et al, 2022 ; Xu et al, 2022 ). Studies also have found a relationship between social media addiction, phubbing, and cognitive flexibility (Gupta & Saha, 2020 ; He et al, 2022 ; Rachman, 2021 ). We propose a new model based on theoretical and empirical evidence, which examines both the mediator and moderator effects of cognitive flexibility in examining the relationship between social media addiction and phubbing in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally to the aforementioned theoretical framework, empirical studies have shown that social media addiction predicts phubbing (Chi et al, 2022 ; Rahman et al, 2022 ; Xu et al, 2022 ). Studies also have found a relationship between social media addiction, phubbing, and cognitive flexibility (Gupta & Saha, 2020 ; He et al, 2022 ; Rachman, 2021 ). We propose a new model based on theoretical and empirical evidence, which examines both the mediator and moderator effects of cognitive flexibility in examining the relationship between social media addiction and phubbing in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cognitive flexibility enhances the ability of individuals to adapt their behavior in accordance with situational factors, which facilitates appropriate behavioral responses (Martin & Rubin, 1995 ). The ability to gain this flexibility can reduce the risk of behavioral problems (e.g., social media addiction) (He et al, 2022 ; Sagar, 2021 ). The study has been carried out with young adults who are considered to be more at risk for behavioral problems (Blacher & McIntyre, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, attention deficit among college students significantly and positively predicted the severity of social media addiction ( 47 , 48 ). Cognitive flexibility and sustained attention have been significantly and negatively associated with social media addiction in college women ( 49 ). Moreover, attention control deficits have become a risk marker for the anxiety onset and persistence ( 50 , 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to behavioral and psychological concerns and adversely affect an individual's mental, social, and emotional well-being [9]. Studies show that, among teenagers who use social media, around 12% exhibit signs of social media addiction [10]. This addiction may affect various aspects of life.…”
Section: Introductionmentioning
confidence: 99%